HIV Vaccine Preparedness among Men Who Have Sex with Men in Taiwan: Sociocultural and Behavioral Factors. (21st March 2019) - Chuang, Deng-Min; Newman, Peter Adam; Weaver, James
In Taiwan, men who have sex with men (MSM) are at disproportionate risk of HIV infection. We examined awareness and acceptability of future HIV vaccines. From July to August 2014, we conducted a cross-sectional survey with MSM recruited through community-based organizations (CBOs) in 2 cities. Among 200 participants (mean age, 27.6 years), half reported multiple partners and one-third condomless anal sex (past 3 months); 12% were HIV-positive. Traditional Chinese medicine (TCM) use was reported by 42.7%. Over two-thirds (69.0%) were aware of HIV vaccine research, but less than half (43.8%) would accept an HIV vaccine if available. In multivariable analysis, higher educational attainment, >5 sex partners, and TCM use were positively associated with HIV vaccine awareness. Culturally informed HIV vaccine preparedness in Taiwan may be supported by a complementary approach to TCM and HIV prevention technologies, tailoring information for MSM with lower education and targeting those at high risk through gay-identified CBOs.